1997
DOI: 10.1210/jc.82.6.1757
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Concentration of Soluble CD30 in Patients with Graves' Disease and Hashimoto's Thyroiditis

Abstract: This study investigated serum levels of the soluble form of CD30 (sCD30), which is mainly secreted from T helper 2(Th2) cells, in autoimmune thyroid diseases. The possible relationship of sCD30 to autoantibody production was also evaluated. Serum levels of sCD30 were determined by an enzyme-linked immunosorbent assay in 71 patients with Graves' disease, 37 patients with Hashimoto's thyroiditis, and 21 normal donors. Compared with normal subjects (7.1 +/- 4.5 U/mL), sCD30 was increased in patients with Graves' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Thus, it is reasonable to speculate that the disease may be dependent on Th2 predominance. Our recent results of increased serum IL-5 and soluble CD30 concentrations in Graves' disease (8,9) support this Th2 predominant hypothesis. However, reported data using the thyroid gland from Graves' disease do not always support this.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, it is reasonable to speculate that the disease may be dependent on Th2 predominance. Our recent results of increased serum IL-5 and soluble CD30 concentrations in Graves' disease (8,9) support this Th2 predominant hypothesis. However, reported data using the thyroid gland from Graves' disease do not always support this.…”
Section: Discussionsupporting
confidence: 76%
“…Mouse Th2 cells secrete type 2 cytokines: IL-4, (7). Recently, we reported that soluble CD30 and IL-5 were IL-5, IL-6, IL-9, IL-10, and IL-13, and promote produc-increased in Graves' disease and Hashimoto's thyroiditis, tion of antibodies, Human Thl and Th2 cells produce cy-and suggested that the type-2 immune response is importokines in a similar pattern, although the synthesis of IL-tant in the pathogenesis of autoimmune thyroid diseases 2, IL-6, IL-10, and IL-13 is not so tightly restricted to a (8,9). The high serum levels of soluble CD30 and IL-5 may single subset as in mouse T cells (2).…”
mentioning
confidence: 99%
“…Patients with pathological conditions, including lymphoproliferative disorders [12,13], viral infections [14,15] or autoimmune diseases [16,17] exhibit increased serum levels of sCD30, mainly in association with advanced disease and poor prognosis [3]. The quantitation of serum CD30 in patients waiting for a kidney transplant has shown that sCD30 is an excellent pre-transplant predictor of kidney graft outcome, allowing the identification of high-risk recipients even in the absence of preformed anti-HLA antibodies [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with Graves’ disease, peripheral eosinophil counts were significantly increased [4]. Furthermore, serum concentrations of interleukin (IL) 5 [5], soluble CD30 [6], IgE [7]and eosinophil-derived neurotoxin were increased [8]. Moreover, it has recently been clarified that the association of seasonal allergic rhinitis was frequent in Graves’ disease and rare in painless thyroiditis [9].…”
Section: Introductionmentioning
confidence: 99%